Does Immigration Increase Concerns about the Provision of Public Services? Evidence from Colombia - Vega-Mendez, Catalina; Visconti, Giancarlo (Revista Latinoamericana de Opinión Pública, 2021)
Although South American countries have experienced unprecedented regional migration in the last decade, there is little research on the impact of these demographic changes on citizens’ political preferences. Does exposure to immigration affect native residents’ concerns about the provision of public services? To address this question, we use survey data from the AmericasBarometer in Colombia before and after the immigration wave generated by the 2015 political and economic crisis in Venezuela. We implement a difference-in-differences design to estimate the effect of distance from border crossings between Colombia and Venezuela on respondents’ concerns about the provision of healthcare and education after the large and rapid influx of immigrants. We find that, after 2015, respondents living closer to a border crossing are more likely to identify a lack of provision of health services, though not education, as one of their primary concerns. These results have relevant political implications since previous research has shown that a fiscal burden on public services can trigger anti-immigration attitudes in host communities.